Evaluation of Philips and Ziegler-Natta high-density polyethylene degradation during processing in an internal mixer using the chain scission and branching distribution function analysis - Pinheiro, Luís A.; Chinelatto, Marcelo A. [UNESP]; Canevarolo, Sebastião V. (Elsevier B.V., 2006)
The oxidative and thermo-mechanical degradation of HDPE was studied during processing in an internal mixer under two conditions: totally and partially filled chambers, which provides lower and higher concentrations of oxygen, respectively. Two types of HDPEs, Phillips and Ziegler-Natta, having different levels of terminal vinyl unsaturations were analyzed. Materials were processed at 160, 200, and 240 degrees C. Standard rheograrns using a partially filled chamber showed that the torque is much more unstable in comparison to a totally filled chamber which provides an environment depleted of oxygen. Carbonyl and transvinylene group concentrations increased, whereas vinyl group concentration decreased with temperature and oxygen availability. Average number of chain scission and branching (n(s)) was calculated from MWD curves and its plotting versus functional groups' concentration showed that chain scission or branching takes place depending upon oxygen content and vinyl groups' consumption. Chain scission and branching distribution function (CSBDF) values showed that longer chains undergo chain scission easier than shorter ones due to their higher probability of entanglements. This yields macroradicals that react with the vinyl terminal unsaturations of other chains producing chain branching. Shorter chains are more mobile, not suffering scission but instead are used for grafting the macroradicals, increasing the molecular weight. Increase in the oxygen concentration, temperature, and vinyl end groups' content facilitates the thermo-mechanical degradation reducing the amount of both, longer chains via chain scission and shorter chains via chain branching, narrowing the polydispersity. Phillips HDPE produces a higher level of chain branching than the Ziegler-Natta's type at the same processing condition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: chain scission; chain branching; HDPE; internal mixer; thermo-oxidative degradation; average number of chain scission and branching CSBDF